CHEMICAL COMPOSITION, IN VITRO ANTIBACTERIAL, AND ANTIOXIDANT ACTIVITY OF ESSENTIAL OIL FROM LEAVES OF AJUGA PARVIFLORA BENTH - Kumar, Sanjay; Javed, Mohammad S; Kumar, Pawan; Kumar, Rishendra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of our study was to evaluate the phytogenic chemical compounds and assess their antibacterial and antioxidant activity of essential oil of Ajuga parviflora Benth. growing in the Himalayan region. Methods: In the present study, the phytochemical constituents of essential oil were isolated by steam distillation and screened by gas chromatography (GC) and GC–mass spectrometry (GC-MS) analysis from A. parviflora is rich in oxygenated monoterpenoids and sesquiterpenoids. The essential oil was further evaluated for their antibacterial by well-diffusion method and antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay at various concentrations. Results: The major chemical constituents were α-cadinol (21.36%), α-muurolol (14.2%), cubebol (12.76%), germacrene D-4-ol (9.6%), germacrene D (4.32%), farnesyl acetate (3.58%), longifolol acetate (2.76%), and β-bourbonene (2.35 %) whereas monoterpenoids were minor constituents. The zone of inhibition (ZOI) shown by essential oil against test bacterial strains at concentration of 500 μg/ml to Gram-negative bacteria Pseudomonas aeruginosa (5.6 mm), Escherichia coli (5 mm), Salmonella typhimurium (8.6 mm), and Proteus vulgaris (10.7 mm) and Gram-positive bacteria Bacillus subtilis (8.3 mm). At the same time, ZOI of standard antibiotic ciprofloxacin against test bacterial strains was P. aeruginosa (9.6 mm), E. coli (14.3mm), S. typhimurium (19.3 mm), P. vulgaris (17.8 mm), and B. subtilis (20.6 mm), respectively. The free radical scavenging property of A. parviflora employed by in vitro assay methods like scavenging activity of DPPH was 81% at 500 μg/ml concentrations, respectively. Conclusion: Our study showed that α-cadinol, α-muurolol, and cubebol as the major components in this oil which was absent in previous findings of A. parviflora and essential oil had potent antibacterial and antioxidant activity, respectively.